Complete mesocolic excision for right sided colonic carcinoma - Our Experience in tertiary care hospital - Mondal, Samiron Kumar; Roy, Sharmistha; Uddin, Mohammad Saif; Murshed, Mahbub; Bashar, Abul (Journal of Surgical Sciences, 2019)
Background: The concept of Complete Mesocolic Excision(CME) as a surgical techniquefor colonic carcinoma.was first introduced in the west in 2008. CME follows the sameprinciple as Total MesorectalExcision(TME) in rectal carcinoma. We have adopted this newtechnique since 2014. Objective: Here we describe the CME technique in open and laparoscopic right hemicolectomy,and our initial experience of the surgery. Methods: This is a prospective observational study. Data collected from 24 patientsadmitted under our care in BIR DEM General Hospital from January 2015 to January 2017with carcinoma caecum or ascending colon. Results: Out of 24 patients 14 patients opted for laparoscopic right hemicolectomy and 10patients choose open right hemicolectomy. In laparoscopic right hemicolectomy with CMEthe mean operating time was 152 minutes, amount of blood loss ranges 70-100ml.Number of lymphnodes removed enbloc with specimen 25-30(mean27). Distance oftumor from mesenteric margins at the point of vascular tie 11-15 cm. In open righthemicolectomy with CME mean operating time was 142 minutes, estimated blood loss120-300 ml, harvested lymph nodes within mesocolic envelop 24-31(mean27), anddistance of tumor from vascular tie is 9-15 cm. there is one major complication of uretericinjury. Histopathology shows resection margin are free of tumor in all except 2 cases. Conclusion: Right hemicolectomy with CME in both open and laparoscopic approach canbe easily adopted by general surgeons and colorectal surgeons who are performing'standard technique' or 'conventional technique' routinely for right hemicolectomy. Withthe encouraging results available from centers who are routinely performing CME incolonic surgery it is now considered as the new bench mark of quality of standard colonicsurgery. Journal of Surgical Sciences (2017) Vol. 21 (1) :15-18